A new species of Sonerila Roxb. (Melastomataceae) from Kerala, India - Narayanan, M. K. Ratheesh; Mini, V.; Shaju, T.; Sujana, K. A.; Joseph, Jayesh P.; Alfarhan, Ahmed H.; Sivadasan, M. (Phytotaxa, 2013)
Sonerila veldkampiana, a new species of Melastomataceae collected from an exposed, high-elevation rocky grassland in Kerala, India is described and illustrated. It resembles S. rotundifolia, but differs in having several important characters like pilose leaf-lamina, terete and glabrous peduncle, inflorescence with 10–35 flowers in branched or unbranched scorpioid cymes, an obscurely ridged hypanthium, long acuminate anthers with a deeply cordate base, and seeds with a sub-excurrent raphe.